Summary of Known Genetic and Epigenetic Modification Contributed to Hypertension - Tiar Masykuroh Pratamawati; Idrus Alwi; null Asmarinah (International Journal of Hypertension)
Hypertension is a multifactorial disease due to a complex interaction among genetic, epigenetic, and environmental factors. Characterized by raised blood pressure (BP), it is responsible for more than 7 million deaths per annum by acting as a leading preventable risk factor for cardiovascular disease. Reports suggest that genetic factors are estimated to be involved in approximately 30 to 50% of BP variation, and epigenetic marks are known to contribute to the initiation of the disease by influencing gene expression. Consequently, elucidating the genetic and epigenetic mediators associated with hypertension is essential for better discernment of its pathophysiology. By deciphering the unprecedented molecular hypertension basis, it could help to unravel an individual’s inclination towards hypertension which eventually could result in an arrangement of potential strategies for prevention and therapy. In the present review, we discuss known genetic and epigenetic drivers that contributed to the hypertension development and summarize the novel variants that have currently been identified. The effect of these molecular alterations on endothelial function was also presented.